The Experience of Home Parenteral Therapy: A Thematic Analysis of Patient Interviews - Marko Puzovic; Hana Morrissey; Patrick A. Ball (MDPI AG, 2023)
Background: A limited number of studies have explored patients' experience with home parenteral (injectable) therapy (HPT) in the UK. Aim: To explore the immediate-, short-, and long-term experience of patients with self-management of any home parenteral therapy with the intention for developing a guideline for service development in the United Kingdom. Methods and design: An interview-based study of patients receiving HPT. Invitations were posted to all patients on the hospital HPT register. The sessions were conducted by telephone for all consenting patients. The interviews were recorded, transcribed, and analysed thematically. Participants completed the 'Health Education Impact Questionnaire' (heiQ) before and after the education session. Results: Of the 640 patients invited to participate in the study, 45 (7%) patients completed the interviews and the education session. An interview analysis revealed that the patients' experiences of HPT were generally positive, but the levels of training and support received showed wide individual variations. The patients had experienced periods of doubt and uncertainty, where they would have appreciated quick access to professional advice to alleviate their concerns. There was a reliable positive change (10.5-18.4%) from before and after the education sessions in six out of the eight domains on the heiQ questionnaire (health-directed behaviour, self-monitoring and insight, constructive attitudes and approaches, skill and technique acquisition, social integration and support, and emotional distress) and moderate change in two domains (5.3% in positive and negative engagement in life, and 2.6% in health services navigation). Conclusion: Self-administered parenteral therapy at home is a valuable option, but training and preparation standards should be optimised across hospitals and the wider NHS.